2010
DOI: 10.1242/jcs.065433
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization ofnumr-1andnumr-2: genes that increase both resistance to metal-induced stress and lifespan inCaenorhabditis elegans

Abstract: SummaryTo define the mechanisms involved in the molecular response to the carcinogenic metal cadmium, two novel metal-inducible genes from C. elegans were characterized: numr-1 and numr-2 (nuclear localized metal responsive). numr-1 and numr-2 sequences and cellular patterns of expression are identical, indicating that these are functionally equivalent genes. Constitutive transcription of numr-1 and numr-2 is developmentally regulated and occurs in the intestine, in head and tail neurons, and vulva muscles. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 71 publications
(70 reference statements)
0
59
1
Order By: Relevance
“…and its response to pristine Ag-MNP and AgNO3 is indicative that some of the effects are also due to dissolved ions (Tvermoes et al, 2010). Our previous study showed that the dissolved Ag released from sAg-MNP (0.43%) over 24 hr is more than 13 times lower than from pristine Ag-MNP (5.8%) (Starnes et al, 2015), which would explain why we did not observe up-regulation in numr-1 expression in response to sAg-MNP .…”
Section: Toxicity Using Mutant Strains and Rna Interferencementioning
confidence: 49%
See 1 more Smart Citation
“…and its response to pristine Ag-MNP and AgNO3 is indicative that some of the effects are also due to dissolved ions (Tvermoes et al, 2010). Our previous study showed that the dissolved Ag released from sAg-MNP (0.43%) over 24 hr is more than 13 times lower than from pristine Ag-MNP (5.8%) (Starnes et al, 2015), which would explain why we did not observe up-regulation in numr-1 expression in response to sAg-MNP .…”
Section: Toxicity Using Mutant Strains and Rna Interferencementioning
confidence: 49%
“…The fourth gene, nuclear metal responsive gene (numr-1), is shared between Ag-MNP and AgNO3 and was up-regulated in both exposures, but showed no effect in sAg-MNP exposure. Numr-1 is a nuclear localized metal response gene and therefore should be closely related due to toxicity from metal ion exposure (Tvermoes et al, 2010).…”
Section: Qrt-pcr Confirmationmentioning
confidence: 99%
“…As DAF-16 migration from the cytosol to the mitochondria is essential for the activation and expression of antioxidant enzymes, such as SOD, the absence of this transcription factor likely generates an imbalance in the pro-oxidant/antioxidant homeostasis, causing increased ROS production, mitochondrial dysfunction, cell death and, consequently, shorter life-span. Reinforcing this hypothesis, pro-oxidant agents such as paraquat and cadmium reduce life-span as well as DAF-16 protein levels (Guan et al, 2010; Tvermoes et al, 2010). In order to determine which step in the DAF-16 cascade was negatively modulated by Mn, we analyzed the levels of the insulin-like receptor DAF-2; the levels of the intermediary kinase AKT; and also a DAF-16 target, SOD-3, a mitochondrial iron/manganese-dependent antioxidant enzyme.…”
Section: Discussionmentioning
confidence: 82%
“…The mechanism behind heavy-metal toxicity is not well understood, but it is thought that heavy-metal ions cause damage to the cell by inactivating and denaturing proteins, and by promoting the formation of reactive oxygen species [67-69]. The thiol tripeptide glutathione, a class of cysteine-rich proteins called metallothioneins, and other larger metal-binding proteins protect the cell from heavy-metal stress by chelating and sequestering metal ions [67, 69, 70]. Heavy-metal stress also activates the expression of cell repair mechanisms, including heat-shock proteins [70].…”
Section: Stress Responses In C Elegansmentioning
confidence: 99%